Peran Religiusitas terhadap Niat Beli pada Generasi Z: Kepercayaan Sebagai Variabel Mediasi - Kartini, Lidwina; Tjahyadi, Rully Arlan (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2024)
The need for halal products, especially food and beverage products, is increasing in Indonesia because the majority of the Indonesian population is Muslim. Generation Z is a group that contributes to the large increase in consumption of halal food products. One of the factors that can influence consumers’ purchase intention on halal food products comes from within the consumers themselves, such as religiosity. This study aims to analyze the relationship between religiosity and purchase intention of halal food products among the Generation Z who lives in Bandung and trust as a mediating variable in this relationship. The population of this study is the Generation Z Muslims aged 17 to 29 years in the city of Bandung and the sample taken is 150 respondents. The data were obtained through the distribution of the questionnaire instrument which was analyzed using the Path Analysis method. The results of this study indicate that religiosity has a significant effect on trust; religiosity and trust affect the purchase intention of halal food products; trust mediates the relationship between religiosity and purchase intention.